Young Talent Ecopreneurship Awareness Model: Personal Character, Digital Skills, and Universities Shaping Ecopreneurial Intention - Sianipar, Martin Yehezkiel; Welly, Yerisma; Ferary, Dorothy (Ilomata International Journal of Management, 2025)
The urgency of this research lies in the importance of preparing young talents to become agents of change in supporting sustainable development. In the future demographic bonus period, the involvement of students as young talents in a sustainable economy and environmentally based innovation is the key to a sustainable future. The aim of this research is to identify the factors that shape students' intentions to become ecopreneurs, as well as to evaluate the role of personal character, digital skills, and higher education institutions in shaping these intentions. This research uses mixed-methods approach, the research stages include: literature study, qualitative data collection, quantitative data collection, data analysis, data integration and interpretation, data presentation, and drawing conclusions. The research results show that the role of personal character and digital skills have a positive and significant influence, but higher education institutions have a positive and insignificant influence in shaping students' ecopreneurship intentions. The research implications provide guidance for stakeholders to develop a green entrepreneurial ecosystem to support the regeneration of young entrepreneurial talents and the development of green talents. In addition, this research provides a theoretical contribution with a better understanding of the factors that shape students' awareness of their intention to become ecopreneurs through the role of personal character, digital skills, and higher education institutions.